Land Use Improvement as the Drought Mitigation to Manage Climate Change in the Dodokan Watershed, Lombok, Indonesia - Nandini, Ryke; Kusumandari, Ambar (MDPI, 2022)
The Dodokan watershed is one of the priority watersheds on Lombok Island, which is a mainstay for providing water for the community but has a high vulnerability to drought. This condition causes disruption to the fulfillment of water needs, so it needs to be anticipated early with mitigation actions. Understanding the trend of drought is needed as a basis for developing mitigation measures, especially related to land use in the watershed. This study aims to analyze the hydro-meteorological drought trend that occurred from 2009 to 2020 and to find out the role of land use improvement in mitigating drought, which is predicted in the next 10 years. The Thornthwaite–Mather method was used for drought analysis, and its predictions for the next 10 years were determined by using trend analysis. Land use simulation using a spatial analysis was carried out as an effort to prepare for drought mitigation actions. The results show that the drought in the Dodokan Watershed has increased in the period between 2009–2020 and is predicted to continue to increase. Land use improvement by restoring the forest is a more appropriate mitigation method to overcome the drought than rearranging the agricultural land on slopes above 25. The simulation results have succeeded in increasing the water surplus and reducing the water deficit in 2030 so that it can be used for drought mitigation in the Dodokan watershed. © 2022 by the authors.